To the Question of Compiling of the Rating Assessment Technique of Insurance Companies - Ulybina, L.K.; Yessengeldin, B.S.; Serikova, G.S.; Kalkabaeva, G.M. (BUKETOV BUSINESS REVIEW, 2017)
The purpose of insurers’ rating creation is to provide ensuring transparency of the results of insurance companies’ activities and determination of level of their financial reliability. General approaches in methodology of compiling of insurance companies rating by various foreign agencies are determined. The indicators characterizing fields of insurance companies’ activity are analyzed: insurance, investment and financial. The indicators of an insurance activity regarding the insurance payments collection, the insurance indemnity payments and securing formation of insurance reserves are considered. The indicators of investing activities of an insurance company regarding placement of insurance reserves are characterized. The indicators characterizing financial activities of an insurance company regarding maintenance of liquidity, solvency and profitability are highlighted. The authors in article determined the problems of creation of a rating assessment technique of insurance companies’ activities. The complex analysis of indicators of insurance companies’ activities is performed, the stages of its carrying out are allocated. Based on the indicators usage which characterizes the fields of insurance companies’ activity the rating assessment technique of insurance companies is developed. The rating assessment technique of insurance companies is presented in the form of the system consisting of consecutive stages, each of which represents the logical sequence of the actions providing creation of insurers’ rating. Implementation of this technique in insurance practice would provide transparency of insurance companies’ activities, increase the trust of insurers to them and to promote development of insurance system.